Enzymatic activity of endophytic fungi of six native seedling species from Doi Suthep-Pui National Park, Thailand - Lumyong S. (2014)
Endophytic fungi were isolated from the stems, petioles, midribs, and leaves of seedlings of six native tree species collected from Doi Suthep-Pui National Park, Thailand. Endophytes were isolated from all tissue samples investigated, and taxa included five ascomycetes, eight anamorphic taxa, and numerous sterile mycelia. Twenty-six strains were tested for their ability to produce cellulase, mannanase, proteinase, and xylanase. The ability to produce these enzymes was distributed amongst the strains tested. Rainforest seedlings supported a diverse array of endophytes that have a wide range of enzymatic activities. The implication of enzyme production in relation to lifestyle abilities of the endophytes is discussed.